Outcomes of Trabeculectomy with 5-Fluorouracil at a Nigerian Tertiary Hospital - Olusola O Olawoye; Adeyinka O Ashaye; Aderonke M Baiyeroju; Christopher C Teng; Jeffrey M Liebmann; Robert Ritch (Journal of Ophthalmic & Vision Research, 2013)
Purpose: To report the outcomes of trabeculectomy with adjunctive 5-Fluorouracil (5- FU) at a Nigerian tertiary hospital. Methods: In this prospective study, all patients with glaucoma undergoing trabeculectomy with 5-FU at the University College Hospital, Ibadan, Nigeria, from June 2009 to May 2010 were enrolled. Each patient had a complete ophthalmic evaluation. Intraocular pressure (IOP), visual acuity (VA) and complications post-trabeculectomy were assessed at one year. Success of the procedure was defined as complete when no additional medications were required to achieve an IOP of ≤18mmHg, or qualified when additional medications were required to achieve the same goal. Results: A total of 47 eyes of 31 patients with mean age of 48.9±19.6 (range 14-77; median 52) years including 21 (67.7%) male subjects underwent trabeculectomy with 5-FU. Mean presenting IOP was 31.8±12.2 mmHg. Mean deviation (MD) on Humphrey visual fields was -15.9±9.7dB with the majority of the patients (18 subjects 58.1%) presenting with advanced glaucoma based on MD worse than -12dB and severe glaucomatous optic neuropathy (cup to disc ratio of 0.9-1.0). At 1 year postoperatively, 95.1% achieved qualified success while 83% had complete success. Conclusion: This prospective study adds to the existing knowledge that trabeculectomy with 5-FU is effective at controlling IOP in Nigerian patients.